Determining the Pulping Conditions and Properties of Unbleached Pulp from Uruguayan Pinus Taeda - Palombo, Viviana; Clavijo, Leonardo; Cabrera, Maria Noel (Ingeniería, 2024)
Context: In Uruguay, numerous Pinus taeda plantations are at final-turn age, but they still do not have commercial destination and are exported as green-wood logs. For the development of this sector, it is necessary to strive towards a comprehensive processing of this resource. Method: This work focused on analyzing the use of Pinus taeda wood available in the country to produce brown kraft pulp with a kappa number of 80, which can be used to make packaging paper. As raw materials, we employed by-products from the mechanical wood-transformation industry (wood chips and thinning wood) and final-turn wood. Pulping tests were carried out, varying the alkali charge and the H-factor while aiming for a kappa number of 80. The viscosity, pulping, and rejection yield were measured in the pulps, and the pH and residual alkali content were evaluated in black liquor. Results: Based on the results, the best pulping conditions were an active alkali charge of 14% (Na2O) and an H-factor of 1260 for sawmill chips and thinning wood, as well as an active alkali charge of 14% (Na2O) and an H-factor of 1080 for final-turn wood. The pulp obtained with sawmill chips exhibited the most resistant fibers, and the final-turn wood pulp was the most sensitive to the refining process. Under the aforementioned conditions, the paper properties of laboratory-produced pulp are comparable with those of commercial pulp. Conclusions: This indicates that it is technologically possible to produce brown kraft pulp from Uruguayan Pinus taeda wood, with adequate quality to produce packaging paper